Design and application of Ti4N3Tx-functionalized bipolar membranes for sustainable acid and base production via BMED system - Halisdemir, Umay; Celik, Aytekin; Yegin, Mustafa; Kose, Yusuf; Hanay, Ozge (Springer, 2026)
In this study, Ti(4)N(3)Tx MXene was successfully synthesized from the Ti4AlN3 MAX phase via a salt etching method and employed as a catalyst in the fabrication of bipolar membranes (BPMs) for application in bipolar membrane electrodialysis (BMED) systems. Structural and physicochemical characterization confirmed the successful synthesis of MXene and the integration of the material into the BPMs. Water uptake analysis revealed a significant enhancement (50-80%) in water absorption in MXene-modified membranes compared to MXene-free counterparts. Contact angle measurements indicated increased surface hydrophilicity, with values decreasing from 73.65 degrees (no MXene) to 62.39 degrees and 55.63 degrees with the incorporation of 1 g and 0.3 g MXene, respectively. Performance evaluations in synthetic brackish water and reverse osmosis (RO) concentrate showed that BPMs containing MXene achieved significantly higher acid and base recoveries. In brackish water, Log [H+] recovery increased up to 4.5-fold and Log [OH-] recovery up to 2.4-fold compared to the control membrane. Similarly, in RO concentrate, Log [H+] and Log [OH-] recoveries increased by up to 2.5-fold and 2.75-fold, respectively. These enhancements are attributed to the high conductivity and rich surface functionalization of Ti(4)N(3)Tx MXene, which effectively improved ion transport and overall BPM performance. The findings highlight the potential of MXene-based BPMs as efficient and durable candidates for advanced ion separation applications.
Keywords: Acid/base recovery; MXene; Ti(4)N(3)Tx; Bipolar membrane (BPM); Electrodialysis